PERSEPSI MAHASISWA JURUSAN AKUNTANSI MENGENAI ETIKA DAN HUKUM PENGGELAPAN PAJAK - Andi Sabirin; Arif Widyatama; Alji Antameng (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine and analyze the Differences in Accounting Department Students' Perceptions regarding Ethics and Tax Evasion Law. In this study, the samples taken were 86 people from 2 campuses. At the Tadulako University campus, the sample was 40 people, and at the Panca Bhakti School of Economics, it was 46 people. Data was collected through a survey obtained by distributing questionnaires to the respondents. The results of this study indicate that the ethics of tax evasion has a significant effect on the tax system. On the other hand, tax justice does not significantly the ethics of tax evasion because there still needs to be emphasis and some points from tax officials for the public to be more precise, and discrimination has a significant effect on tax evasion laws.